Prise en compte de la pluralité des mémoires d’habitants dans la « patrimonialisation » des grands ensembles - Rachid Kaddour (EchoGéo)
The research examines Montchovet and Beaulieu, two of the four contrasting social housing estates composing southeastern Saint-Etienne (France). A local plan carried out in this place, with two aspects. First, it provides the demolition of Montchovet because of its pauperization during the 80s. Second, Beaulieu (socialy mixed) become established as model that can redefine the other social housing estates. These operation is emblematic of a progressive return to the roots and a heritage process. But this project also neglects and erases the histories of the poor, the workers and the immigrants.